PENGARUH METODE MULTISENSORI DALAM MENINGKATKAN KEMAMPUAN MEMBACA PERMULAAN PESERTA DIDIK KELAS II SEKOLAH DASAR - Nurkhaliza, Mery; Mega Diana, Siska; Hariyanto; Sowiyah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by limited empirical research on the effectiveness of multisensory methods in improving beginning reading skills at the elementary school level. The study aimed to examine the effect of the multisensory (VAKT) method on the beginning reading skills of second-grade elementary school students using a quantitative quasi-experimental nonequivalent control group design. The sample consisted of two classes: Class II B, the experimental group, which received multisensory instruction, and Class II A, the control group, which received conventional instruction. Data were collected through a beginning reading skills test and analyzed using the Wilcoxon Signed-Rank Test, the Mann–Whitney U Test, and N-Gain analysis. The results showed a significant improvement in the experimental group following the implementation of the multisensory method, with high effectiveness as indicated by N-Gain results. Although no statistically significant difference was found between the experimental and control groups, descriptive analysis showed that the multisensory method positively supported students’ learning progress. The study concluded that the multisensory method demonstrated effectiveness in enhancing beginning reading skills within the experimental group and was recommended for elementary reading instruction.